Effectiveness of Ethanol Extract Mangosteen Peel (Garcinia Mangostana L.) in Accelerating Post-Tooth Extraction Healing in Wistar Rats - Dong Qian; Florenly Florenly; Liena Liena; Dewi Riastawaty Purba (Budapest International Research and Critics University, 2022)
Tooth extraction will cause a wound in the form of alveolar bone that opens in the oral cavity. Mangosteen peel has various pharmacological effects such as anti-inflammatory, antioxidant, antidiabetic, and antibacterial. The goal of this study was to find out the effectiveness of Mangosteen Peel Ethanol Extract (Garcinia mangostana L.) 45% with 90% in speeding up the healing time of post-tooth extraction wounds in Wistar rats. This type of research is an experimental laboratory with a post-test pattern only control group design. Conducted at the Laboratory of Pharmacology & Laboratory of Traditional Medicine Faculty of Pharmacy, University of North Sumatra January-March 2021. The animal is a male Wistar rat of 32 who is physically healthy. The size of the sample is determined by Federer's formula, the minimum sample size for each treatment is 16 rats. The results of the study that there is a significant relationship between the amount of fibroblast tissue per field of view in Wistar Rats after tooth extraction with the administration of mangosteen peel (Garcinia mangostana L.) with a concentration of 45% and mangosteen peel (Garcinia mangostana L.) concentration 90%, p = 0.036 (p<0.05). Mangosteen skin extract (Garcinia mangostana L.) is 45% and 90% effective in speeding up wound healing time after extraction of rat teeth Wistar. Mangosteen skin extract (Garcinia mangostana L.) is 90% more effective than turmeric extract (Curcuma longa) 45% in speeding up wound healing time post-extraction of rat teeth Wistar due to the flavonoid content in mangosteen skin extract (Garcinia mangostana L.) 90% which helps accelerate wound healing higher than skin extract Mangosteen (Garcinia mangostana L.) 45%.